Program Kelas Literasi sebagai Upaya Meningkatkan Minat Baca Peserta Didik - Rafida Saputri; Makhromi (Indonesian Journal of Humanities and Social Sciences, 2022)
This study examines how the implementation of literacy classes in improving students' reading skills at SDITA Kediri. Literacy in schools has an important role in fostering reading interest in students as a whole to make the school a learning organization and to make the school environment literate by presenting various reading books and accommodating various strategies so that students' reading interest increases. This research uses qualitative research methods with a descriptive approach. Data collection methods obtained through interviews, observation and documentation. The results showed that if the literacy class program in schools is implemented properly, it will have an important role in increasing students' reading interest, especially the role as a media for students to habituate reading.